The onset of the flash transition in single crystals of cubic zirconia as a function of electric field and temperature. (June 2017) - Yadav, D.; Raj, R.
Abstract: We have measured the onset of flash in cubic zirconia single crystals, in experiments similar to flash sintering. This behavior is compared with results on sintering of porous specimens of 8–10 mol% cubic zirconia. The single crystals flash at lower temperatures and lower electric fields, which does not support an unalienable role for particle-particle interfaces in the flash mechanism. The flash onset in single crystals occurs at similar values of the power density as the powder samples, which, furthermore, lies in the same range as the onset of the flash transition in several oxides. Graphical abstract: